STRUKTUR KOMUNITAS IKAN KARANG DI PULAU UNGGEH KABUPATEN TAPANULI TENGAH PROVINSI SUMATERA UTARA - YULIANA HANDAYANI GEA; Zulham Apandy Harahap (Program Studi Manajemen Sumberdaya Perairan, Fakultas Pertanian Universitas Sumatera Utara, 2018)
Reef fish research in Unggeh Island waters aims to determine the species composition, abundance, distribution, and community structure of reef fish in these waters. Data collection was carried out in December 2017 and April 2018 at four stations in Unggeh Island waters. Data was collected using Underwater Visual Census (UVC) and transect methods (Underwater Photo Transec, UPT) with SCUBA equipment. Total species of reef fish in December 2017 were collected as many as 36 species representing 10 families. And in April 2018 there were 22 types representing 9 families. Diversity Index values range from 1.36 to 3.23. Diversity index (H ') in December 2017 and April 2018 each valued at 1.50-2.41 (medium category) and 2.04-2.58 (medium category). The uniformity value of € in December 2017 and April 2018 is worth 0.63-0.5 (high category) and 0.79-0.89 (high category), respectively. Dominance index (C) in December 2017 and April 2018 each value 0.12-0.42 (low category) and 0.16-0.18 (low category).Keywords: Reef Fish, Unggeh Island, Coral reef ecosystems